Гуманітарна та просвітницька діяльність Українських січових стрільців на Волині (1916 – початок 1918 р.) - Лазарович, Микола; Lazarovych, Mykola (My University, 2016)
Проаналізовано культурно-просвітницьку та гуманітарну діяльність Українських січових стрільців на Волині під час Першої світової війни. Значну увагу приділено становленню Українських січових стрільців як національного військового підрозділу, а також заснуванню українських шкіл. Визначено вплив діяльності УСС на поглиблення національної свідомості волинян.This thesisis dedicated to the struggle of Ukrainian Sich Riflemen for the Ukrainian independence during the First World War. Special attention is paid to the process of becoming legion of Ukrainian Sich Riflemen as a national military and political unit. He, along with armed struggle actively engaged in ideological and political activity. The main directions of cultural and artistic and educational work USS shown their influence on the formation and deepening of national consciousness of the Ukrainian society is determined. Humanitarian and cultural and educational activities of Ukrainian Sich Riflemen in the Volyn region in 1916 - early 1918 investigated.
Humanitarian and Educational Activities of Ukrainian Sich Riflemenin Volyn (1916 - early 1918)
Keywords: УСС; Волинь; просвіта; шкільництво; USS; Volyn; education; schooling; humanitarian activities; national consciousness